2022
DOI: 10.3389/feart.2022.818452
|View full text |Cite
|
Sign up to set email alerts
|

Research on Coal Acoustic Emission Characteristics and Damage Evolution During Cyclic Loading

Abstract: The acoustic emission, energy, and damage evolution of coal samples for three kinds of uniaxial cyclic loading and unloading are deeply analyzed in this study. The evolution of total absorption energy, elastic strain energy, and dissipated energy of coal samples is related to the stress path, and the increasing amplitudes cycle loading has an obvious damage effect on coal samples. During the loading stage, the acoustic emission phenomenon is most active when loading is increasing and the Felicity and post-Kais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Te results showed that the characteristics of the AE waveform parameters well refect the growth behavior of coal HF. Zhili et al [10] studied the AE, energy, and damage evolution of coal samples under three uniaxial cyclic loading and unloading conditions. Based on the Braziliansplitting test and uniaxial and triaxial compression tests, Su et al [11] and Yang et al [12], respectively, studied the evolution of rock failure and AE characteristics under different loading rates, which further deepened the understanding of rock failure process and provided theoretical support for rock stability analysis in mining design and construction.…”
Section: Introductionmentioning
confidence: 99%
“…Te results showed that the characteristics of the AE waveform parameters well refect the growth behavior of coal HF. Zhili et al [10] studied the AE, energy, and damage evolution of coal samples under three uniaxial cyclic loading and unloading conditions. Based on the Braziliansplitting test and uniaxial and triaxial compression tests, Su et al [11] and Yang et al [12], respectively, studied the evolution of rock failure and AE characteristics under different loading rates, which further deepened the understanding of rock failure process and provided theoretical support for rock stability analysis in mining design and construction.…”
Section: Introductionmentioning
confidence: 99%
“…Deep mining is often in the complex environment of high geostress, high karst water pressure and strong mining disturbance [1][2][3][4]. While the coal in the roadway is bearing deep high stress, it is also affected by the repeated disturbance of coal seam group mining and surrounding mining activities [5][6][7][8] so that the internal cracks and damage continue to develop under the stress path of cyclic loading and unloading [9][10][11], resulting in frequent failure of anchor bolt or cable and continuous degrade of structural stability [10,12,13]. Relevant studies [14,15] also show that the strength characteristics and deformation law of coal (rock) under cyclic loading and unloading path are significantly different from bearing characteristics of coal (rock) under uniaxial compression path.…”
Section: Introductionmentioning
confidence: 99%